1995
DOI: 10.1002/jemt.1070300405
|View full text |Cite
|
Sign up to set email alerts
|

Androgen, estrogen, and progesterone receptors in normal and aging prostates

Abstract: Testicular hormones regulate the growth and development of the prostate. The presence of androgen receptors in prostatic tissue and their importance in the normal development of the prostate has been established. Age-related changes in the hormonal milieu, and perhaps steroid hormone receptor profile, could set in motion pathological changes leading to the onset of benign prostatic hyperplasia (BPH) or prostate cancer which primarily affect older men. The accumulation of dihydrotestosterone with age, the reawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 71 publications
(62 reference statements)
2
24
1
Order By: Relevance
“…Consequently, estrogen deprivation significantly reduces prostatic volume in BPH patients (Schweikert et al 1993). Since ERs had only been identified in the prostatic stroma, it was assumed that, at the beginning of BPH, estrogens caused proliferation of the prostatic stroma, and then the hyperplastic stroma induced epithelial cell growth, which in turn enhanced androgen action, because androgen receptors are predominantly localized in the prostatic epithelium (Bashirelahi et al 1979, Srinivasan et al 1995. The presence of ERs in both stroma (ER-) and epithelium (ER-) accounts for a direct estrogen action on the two prostatic compartments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, estrogen deprivation significantly reduces prostatic volume in BPH patients (Schweikert et al 1993). Since ERs had only been identified in the prostatic stroma, it was assumed that, at the beginning of BPH, estrogens caused proliferation of the prostatic stroma, and then the hyperplastic stroma induced epithelial cell growth, which in turn enhanced androgen action, because androgen receptors are predominantly localized in the prostatic epithelium (Bashirelahi et al 1979, Srinivasan et al 1995. The presence of ERs in both stroma (ER-) and epithelium (ER-) accounts for a direct estrogen action on the two prostatic compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have confined this receptor to the stromal compartment of the prostate (Bashirelahi et al 1979, Ehara et al 1995, whereas others have also localized it in the epithelial compartment (Schulze & Claus 1990). There is also no agreement on the association between ER-and prostatic neoplasia, since this receptor has been demonstrated in several prostate cancer cell lines (Carruba et al 1994, Castagnetta & Carruba 1995, Srinivasan et al 1995 but not in others (Brolin et al 1992, Konishi et al 1993, Hobisch et al 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of STUMP are Owing to the derivation of these tumors from the prostatic stroma, [5][6][7] progesterone receptor is frequently present on immunostaining, although estrogen receptor is less commonly positive. C-kit and S-100 were negative in all cases examined.…”
Section: Stumps and Stromal Sarcomasmentioning
confidence: 99%
“…Previous reports have shown that the prostate epithelium predominately expresses estrogen receptor-beta (ER-b) whereas stromal cells predominately express progesterone receptor (PR) and estrogen receptor-alpha (ER-a). [8][9][10][11] The role of ER-b in prostate carcinogenesis has been described only recently. 4,[12][13][14] Even though its function is not fully understood, and the data in the literature is conflicting, recent evidence suggests that it may have a role in tumor progression.…”
mentioning
confidence: 99%